2022
DOI: 10.1094/phyto-01-22-0028-r
|View full text |Cite
|
Sign up to set email alerts
|

Maize Root Exudates Recruit Bacillus amyloliquefaciens OR2-30 to Inhibit Fusarium graminearum Infection

Abstract: Bacillus spp. can exert plant growth-promoting effects and biocontrol effects after effective colonization, and bacterial chemotaxis toward plant root exudates is the initial step to colonize. Under biotic stress, plants are able to alter their root exudates in order to attract or avoid different types of microbes. Hence, Bacillus chemotaxis toward root exudates after pathogen infection is crucial for exerting their beneficial effects. In this study, B. amyloliquefaciens OR2-30 strain, which exhibited greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The lipopeptides iturin and fengycin exhibit strong antagonistic effects against F. graminearum and are the major antifungal substances produced by Bacillus spp. (Hanif et al, 2019 ; Xie et al, 2022 ). Our HPLC results showed that the deletion of degQ and degU significantly reduced iturin and fengycin yields based on the calculation of peak areas, which corroborate our predictions (Figure 5c,d ).…”
Section: Discussionmentioning
confidence: 99%
“…The lipopeptides iturin and fengycin exhibit strong antagonistic effects against F. graminearum and are the major antifungal substances produced by Bacillus spp. (Hanif et al, 2019 ; Xie et al, 2022 ). Our HPLC results showed that the deletion of degQ and degU significantly reduced iturin and fengycin yields based on the calculation of peak areas, which corroborate our predictions (Figure 5c,d ).…”
Section: Discussionmentioning
confidence: 99%
“…The expression profile of the rice plant defence genes ( LOX1, EXP18, GluA, PAL1, PBZ1, SOD1, PR‐3 , and PR‐4 ) was analyzed after exposure to synthetic VOCs in the pot experiment (Xie et al 2022). The leaf samples were collected after 7 days of exposure to the selected VOCs.…”
Section: Methodsmentioning
confidence: 99%
“…(2021) demonstrated that Bacillus X13, Bacillus X14, and co-inoculation of both strains exhibited a promotion effect on total dry biomass, crude protein content and digestibility in Megathyrsus maximus under drought. According to Xie et al (2022), maize root exudate recruited B. amyloliquefaciens OR2-30 to colonize the rhizosphere and then inhibited the growth of Fusarium graminearum by producing iturins. In our experiments, some Bacillus strains increased the growth of A. inebrians at the seedling emergence (21 days old) and mature stage (grown in the 2:1 vermiculite and black soil mixture for 3 months).…”
Section: )mentioning
confidence: 99%